Natural fiber-mediated epoxy composites – A review. (15th August 2016) - Mittal, V.; Saini, R.; Sinha, S.
Abstract: With growing inclination towards the eco-friendly technology, natural fiber based polymer composite materials have been gaining a lot of momentum nowadays. The present review discusses the much research that has been carried out in the area of the epoxy-based composites reinforced with natural fibers. Influence of the various factors like the fiber content, fiber geometry, fiber size, surface treatment technique, and coupling agent on different properties like mechanical, thermal, behavior towards water absorption and others have been presented. It can be inferred that there is a need and scope for improvement of the surface properties of natural fiber using various methods like physical and chemical treatments, addition of coupling agents, etc. for the manufacturing of the composites having desired properties. These techniques not only modify surface morphology, but also improve other processing parameters like the hydrophilic character of fiber (which is desirable to be low), and hence improve several characteristics such as mechanical properties, thermal stability, water absorption and other considerations of the composites.